Severe Rhabdomyolysis in a 20-year-old Fit Individual: A Case Report and Literature Review - Macêdo, João Pedro Olinda de; Viana, Ana Clara de Oliveira; Moura, Flávio José Dutra de (Brazilian Journal of Case Reports, 2026)
A previously healthy 20-year-old male individual who regularly practiced karate performed moderate physical activity at a gym without adequate hydration. One day after exercising, he developed intense myalgia. After three days, laboratory tests revealed high levels of creatine phosphokinase (CPK), consistent with severe rhabdomyolysis. Other abnormalities were also found, including elevated transaminases and phosphorus. After 5 days, myalgia had been resolved and creatine phosphokinase levels began to decrease, but there was an increase in creatinine and the patient was hospitalized for intravenous hydration. After 1 day of hospitalization, the patient's creatinine normalized and subsequent laboratory tests showed a gradual return of other laboratory markers to normal. We present the pathophysiological mechanisms, diagnosis, and treatment of rhabdomyolysis, highlighting the potential of certain types of exercise to trigger this muscle pathology even in physically active individuals.